2016
DOI: 10.3344/kjp.2016.29.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone or Dexmedetomidine as Local Anesthetic Adjuvants for Ultrasound-guided Axillary Brachial Plexus Blocks with Nerve Stimulation

Abstract: BackgroundThe purpose of this study was to evaluate the effect of dexamethasone or dexmedetomidine added to ropivacaine on the onset and duration of ultrasound-guided axillary brachial plexus blocks (BPB).MethodsFifty-one ASA physical status I-II patients with elective forearm and hand surgery under axillary brachial plexus blocks were randomly allocated to receive 20 ml of 0.5% ropivacaine with 2 ml of isotonic saline (C group, n = 17), 20 ml of 0.5% ropivacaine with 2 ml (10 mg) of dexamethasone (D group, n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 18 publications
3
50
2
Order By: Relevance
“…This study is consistent with the finding of Lee et al, Esmaoglu et al and Das et al, which showed that the use of DEX as an adjuvant to local anesthesia decreases analgesic consumption dose ( 20 - 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…This study is consistent with the finding of Lee et al, Esmaoglu et al and Das et al, which showed that the use of DEX as an adjuvant to local anesthesia decreases analgesic consumption dose ( 20 - 22 ).…”
Section: Discussionsupporting
confidence: 93%
“…the axillary BPB prolonged the duration of both sensory and motor nerve blocks without any major side effects [24]. Some investigators demonstrated that adding dexamethasone or dexmedetomidine to LAs during axillary BPBs extended the sensory block duration with no significant differences regarding the onset time of sensory block or postoperative complications [10].…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine is a highly selective alpha-2 adrenergic agonist with both analgesic and sedative effects. Perineural injection of dexmedetomidine prolonged the time span of both sensory and motor blocks when added to LAs during the brachial plexus block (BPB) [10]. Many investigators reported faster onset and longer duration of the sensory block when using dexmedetomidine for the greater palatine, axillary brachial, and ulnar nerve blocks [11].…”
Section: Original Articlementioning
confidence: 99%
“…Dexmedetomidine (DEX), a potent and selective α 2 adrenoceptor agonist, was recently shown to prolong analgesic duration when added to local anaesthetics in regional anaesthesia . This effect is related to the enhancement of hyperpolarization‐activation cation currents, which prevents the nerve from returning to resting membrane potential from a hyperpolarized state and subsequent firing .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…6 Dexmedetomidine (DEX), a potent and selective α 2 adrenoceptor agonist, was recently shown to prolong analgesic duration when added to local anaesthetics in regional anaesthesia. [8][9][10][11] This effect is related to the enhancement of hyperpolarization-activation cation currents, which prevents the nerve from returning to resting membrane potential from a hyperpolarized state and subsequent firing. 12 Ghobadifar et al 13 reported that intrathecal DEX may play an important role in mitigating neuropathic pain.However, there has been no report on the effect of long-term repeated usage of DEX in conjunction with local anaesthetics in BPB for CRPS.…”
mentioning
confidence: 99%